2019
DOI: 10.1080/15980316.2019.1649310
|View full text |Cite
|
Sign up to set email alerts
|

An optically efficient full-color reflective display with an electrochromic device and color production units

Abstract: In this paper, we report a full-color reflective display device by combining reflective electrochromic device (ECD) and different color production units (conventional color filter (CF) and transmittance controllable electrochromic color filter (TCECF)). A full-color reflective device with TCECF showed an excellent diffuse reflectance of 47.2% in the white state owing to the high transmittance of TCECF in the bleached state than that of CF (19.5%). This device structure can easily provide various colors with hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Unlike the sample in which opaque colour is determined from reflectance of light, the transparent colour of the film is determined by transmission of light [15]. Such uneven transmittance has caused the films to have a yellow tint, which is enhanced as the film thickness increases.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike the sample in which opaque colour is determined from reflectance of light, the transparent colour of the film is determined by transmission of light [15]. Such uneven transmittance has caused the films to have a yellow tint, which is enhanced as the film thickness increases.…”
Section: Resultsmentioning
confidence: 99%
“…Can colorful EC pixel displays be realized with color filters? Based on this question and innovative concept, Jang H. Kwon et al reported full-color reflective displays based on the RGB color mode, which included both a color filter (CF) and a transmittance controllable EC color filter (TCECF) . The utilized CF and TCECF could selectively transmit visible light, and a black ECD was used to turn the pixels on/off to show the corresponding colors.…”
Section: Electrochromic Pixel Displaysmentioning
confidence: 99%
“…reported full-color reflective displays based on the RGB color mode, which included both a color filter (CF) and a transmittance controllable EC color filter (TCECF). 373 The utilized CF and TCECF could selectively transmit visible light, and a black ECD was used to turn the pixels on/off to show the corresponding colors. In addition, EC leuco dye derivatives with multiple colors (red, green, and blue) were induced in the display to replace the CFs for a higher diffuse reflectance.…”
Section: Lateral Arrangementmentioning
confidence: 99%
“…It does not require a backlight and has a wide viewing angle and memory that retains image information even when the power is turned off [ 4 , 5 , 6 , 7 ]. Recently, various products such as e-books, billboards, information boards, Electronic Shelf Labels (ESLs), and Points of Purchase (POPs) have been developed using e-paper due to its many advantages, such as easy readability [ 8 , 9 , 10 ]. While these advantages meet all the requirements of an ideal display, it is difficult to achieve them in a color display [ 11 ].…”
Section: Introductionmentioning
confidence: 99%